Heterologous Expression of Endo-1,4-beta-xylanaseA from Phanerochaete chrysosporium in Pichia pastoris - Huy, Nguyen Duc (The Korean Society of Mycology, 2011)
The cDNA of endo-1,4-β-xylanaseA, isolated from Phaenerocheate chrysosporium was expressed in Pichia pastoris. Using either the intrinsic leader peptide of XynA or the α-factor signal peptide of Saccharomyces cerevisiae, xylanaseA is efficiently secreted into the medium at maximum concentrations of 1,946 U/L and 2,496 U/L, respectively.